Neonatal mortality outcome and trends: A 6-year retrospective analysis from a North Indian teaching college hospital - Ritu Rakholia; Mohd Maroof; Damini Kharkwal; Gurpreet Singh (Journal of Family Medicine and Primary Care)
Background: India contributes to the highest number of neonatal deaths in the world, a fourth of the world’s total. Targeted interventions can be planned after a specific analysis of region-specific causes if India is to achieve the sustainable development goal (SDG 3.2) of neonatal mortality of 12 per 1000 live births. Material and Methods: A retrospective study of medical records of all neonates admitted in the special care neonatal unit (SCNU) over the 6-year period of 2018–23 at a teaching medical college. Results: A total of 9462 neonates were admitted over the 6-year period. The trends in mortality were encouraging, declining from 19.40% in 2018 to 12.34% in 2023. The reduction was more in outborn (24.32% to 11.68%) than inborn (14.86% to 12.89%) neonates. The low birth rate also declined from 40.77% in 2018 to 25% in 2023. The rate of discharges went up. The trends in etiology of death were uniform over the years with respiratory distress syndrome (RDS) (37.24%), hypoxic-ischemic encephalopathy (HIE) (29.5%), sepsis (16.12%), prematurity (11.45%), and congenital malformations (2.47%) being the chief contributors to death among newborns admitted in SNCU. Conclusion: The trends are encouraging but may be insufficient to meet the target of SDG 3.2. Further targeted intervention to tackle preventable cause, such as perinatal asphyxia, sepsis, better antenatal care, and better management of preterm neonates on mission mode, is need of the hour as they continue to contribute significantly to neonatal mortality.